THE DAMPAK KONFLIK ANTARA PEKERJAAN DAN KELUARGA TERHADAP KINERJA PEKERJA PEREMPUAN DENGAN KEPUASAN KERJA SEBAGAI MEDIATOR DI PT. KALDU SARI NABATI RANCAEKEK - Nurunnadiya Savitri; Hilmiana Hilmiana; Kartono Kartono; Devi Alviani (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
The aim of this study is to explore the relationship between work-family conflict and employee performance, as well as the effects of job satisfaction and work-family conflict on employee performance. For the study, which was conducted at PT. Kaldu Sari Nabati Indonesia Rancaekek Bandung, 195 married female employees from the Production Department were chosen. A questionnaire was used to collect the study's data, and the statistical product and service solutions (SPSS) program was used for the analysis. The results demonstrate that although work-family conflict does not directly and significantly affect employee performance, it does so when job satisfaction is taken into account as a mediator. Furthermore, employee performance is significantly positively impacted by job satisfaction. These results highlight the crucial role that job satisfaction plays in minimizing the detrimental effects of work-family conflict on employee performance.